The content of patient counseling about interchangeable medicines and generic substitution in Finnish community pharmacies - a survey of dispensers - Riikka Rainio; Riitta Ahonen; Johanna Timonen (BMC, 2019)
Abstract Background Generic substitution aims to increase the use of more affordable generic preparations and restrain the growth of medicine expenditures. Pharmaceutical staff plays an important role in generic substitution by implementing substitution and counseling customers. The aim of this study was to explore how Finnish dispensers inform pharmacy customers about interchangeable medicines and generic substitution and what customers ask dispensers about generic substitution and the reference price system. Methods A questionnaire was sent to a random sample of dispensers (n = 1054) working in community pharmacies in spring 2018. The data was analyzed using frequencies, percentages and the Chi-square test and Fisher's exact test. The open-ended questions were analyzed first using inductive content analysis and later with the quantitative methods mentioned above. Results The final study material consisted of 498 questionnaires (response rate 51%). The main topics dispensers always informed customers about were the physician's record in the prescription not to substitute the medicine (69%) and that the prescribed or purchased interchangeable medicine did not belong in the reference price band (59%). Topics mentioned often by dispensers dealt with customer's chance to choose their medicine from among several alternative products (68%) and the manufacturer of the interchangeable medicines (66%). Differences in appearance (33%) or in composition (28%) of interchangeable products were the most common topics mentioned only when the customer asked about them. Of the respondents 17.6% always and 51.4% often informed the customer about the least expensive interchangeable product at the point of dispensing. Customers' questions about the generic substitution and reference price system most commonly (82.4%) concerned the similarity of interchangeable medicines. Conclusions Finnish dispensers provide customers with a wide range of information about different subjects when dispensing interchangeable medicines. Patient counseling generally meets the legislative requirements, except for price counseling. In future, information about generic substitution and interchangeable medicines should continuously be provided to customers both at pharmacies and elsewhere, e.g. through educational campaigns.